Immigrant participation in welfare benefits in the Netherlands - Aslan Zorlu (Institute for the Study of Labor (IZA), 2011)
The efficiency of Dutch welfare system is at the heart of debate as long as immigrants are overrepresented in social welfare benefits during the working age period. This paper examines the degree of participation in social assistance, disability and unemployment benefits across ethnic groups using register data of the entire population in the Netherlands. The analysis shows that migrants are drastically more likely to have a benefit, in particular social assistance and disability benefits. A large part of migrants' dependence can be explained by their background characteristics and immigration history but still a significant unexplained residual is left. Most notably, the probability of welfare use of non-western second generation is about twice as high as the probability of western immigrants, which is a true challenge for policy makers.
urn:nbn:de:101:1-201112136761
Keywords: J15; J32; 330; ethnic minorities; benefits; inactivity; Migranten; Ethnische Gruppe; Sozialhilfeempfänger; Lohnfortzahlung; Niederlande